Photocontrollable Probes for Mitochondrial Protein Profiling. (7th April 2022) - Guo, Shuhong; Yuan, Chaonan; Lang, Wenjie; Hong, Danqi; Liu, Jian; Huang, Jintao; Dong, Jia; Ge, Jingyan
Abstract: The mitochondrion is the core site of cell signaling, energy metabolism and biosynthesis. Here, taking advantage of activity‐based probes, we synthesized two photocontrollable probes (YGH‐1 and YGH‐2 ), composed of a mitochondrial localization moiety "triphenylphosphonium", a photo‐triggered group to achieve spatially and temporally controlled protein capture, and an alkyne group to enrich the labeled protein. Proteomic validation was further carried out to facilitate identification of the mitochondrial proteome in HeLa cells. The results show that half of the identified protein hits (∼300) labeled by YGH‐1 and YGH‐2 belong to mitochondria, and are mostly localized in the mitochondrial matrix and inner mitochondrial membrane. Our results provide a new tool for spatial and temporal analysis of subcellular proteomes. Abstract : Two photocontrollable probes (YGH‐1 and YGH‐2 ) were synthesized and used for mitochondrial proteomic studies. Our results show that the probes can be successfully used for spatial and temporal analysis of subcellular proteomes.